Prognostic impact of the tumor immune microenvironment in pulmonary pleomorphic carcinoma. (March 2021) - Amemiya, Ryosuke; Miyoshi, Tomohiro; Aokage, Keiju; Suzuki, Jun; Hoshino, Hironobu; Udagawa, Hibiki; Tane, Kenta; Sugano, Masato; Kojima, Motohiro; Fujii, Satoshi; Kuwata, Takeshi; Ochiai, Atsushi; et al.
Highlights: Evaluation of the immune microenvironment of pulmonary pleomorphic carcinoma. Comparison of the non-small cell carcinoma component and sarcomatoid component. Higher expression of Programmed death ligand 1 expression in sarcomatoid component. Programmed death ligand 1 expression can be a prognostic factor. Abstract: Introduction: Pulmonary pleomorphic carcinoma (PC) is a rare non-small cell lung carcinoma (NSCLC) and is characterized by sarcomatoid and NSCLC components. This study aimed to characterize the association between immune microenvironmental factors and clinicopathological characteristics of PC. Methods: Eighty consecutive PC patients who had undergone complete surgical resection were enrolled. We calculated the immunohistochemical staining scores for E-cadherin, vimentin, programmed death ligand 1 (PD-L1), and carbonic anhydrase IX in cancer cells and counted the numbers of CD204-positive tumor-associated macrophages (TAMs) and Foxp3-, CD8-, and CD20-positive tumor-infiltrating lymphocytes (TILs). We also examined the association between these scores and the prognostic outcomes. Results: The staining score for PD-L1 in cancer cells and the number of CD204-positive TAMs in the sarcomatoid component were significantly higher than those in the NSCLC component; E-cadherin score in the sarcomatoid component was significantly lower. Patients with high PD-L1 expression in the NSCLC component had significantly longer overall survival (OS) and recurrence-free survival (RFS) than those with low PD-L1 expression in the NSCLC component (OS: p = 0.001, RFS: p = 0.038). Multivariate analysis revealed that high PD-L1 expression in the NSCLC component was an independent favorable prognostic factor for OS (p = 0.018), whereas high PD-L1 expression in the sarcomatoid component was not. The number of CD8-positive TILs was significantly higher in the high PD-L1 expression group than in the low expression group (NSCLC components: p < 0.001). Conclusion: High PD-L1 expression in the NSCLC component may be associated with a favorable prognostic value in pulmonary PC.